The availability degree of educational and training programs design skills for postgraduate students in Faculty of Education of Damascus and Tishreen universities (Damascus University Journal of educational and Psychologyical sciences, 2024)
This research intended to determine the availability degree of educational and training programs design skills for postgraduate students in Faculty of Education, and how changes on (university, degree, gender, and the type of thesis program) variables effect it.To achieve the aims of the research, a descriptive approach was used by designing a survey consists of (24) phrases distributed among three issue areas, and a research sample of (85) students whose thesis’s include designing educational or training programs in Faculty of Education of Damascus and Tishreen universities.Research concluded to the following results:• The availability degree of educational and training programs design skills for postgraduate students in Faculty of Education was average based on following order (program planning skill, program establishing skill, experimental survey of the program and its final design skill).• There’re statistical differences in the availability degree of educational and training programs design skills for postgraduate students in Faculty of Education in favor of Damascus University based on university variable, in favor of PhD students based on degree variable, in favor of educational programs based on type of thesis program.• There aren’t any statistical differences in the availability degree of educational and training programs design skills for postgraduate students in Faculty of Education based on gender variable.
Keywords: Designing Training And Educational Programs; Postgraduate Students